Exploring individual and organizational factors influencing cooperation in commons: a scoping review - Pedrazzini, Sabina; Gurtner, Lilla M.; Aggrey, Vincent; Moser, Stephanie (Frontiers in Psychology, 2025)
Today, humanity faces multiple social and environmental crises that have arguably been caused by mainstream modes of economic organization. Against this background, commons represent a promising, viable alternative that enables people to self-organize to satisfy their needs in a more sustainable way. However, for commons to be successful, their members must cooperate. Despite the importance of cooperation for commoning processes, few studies in the scientific field of the commons have investigated cooperation using an individual-centered approach. To fill this knowledge gap, we conducted a scoping review to gather existing research about individual cooperation. We sought to identify factors that can impact cooperation in commons. We used a keyword search in three online databases to identify papers of interest. For inclusion, papers had to measure cooperation as an outcome variable, assess the impact of one or more factors on cooperation, use adult participants, and be written in English. The application of these criteria led to the inclusion of 135 papers. The included papers enabled us to identify nine factors influencing cooperation that could be divided into two categories. The first category includes individual factors, which depend on individuals' characteristics. These factors are: gender, social status, group identification, values and personality traits, and trust. The second category includes organizational factors, which concern the way individuals are organized as a group. These are: incentives, communication, social norms, and anonymity. We discuss these results vis-à-vis previous commons literature, showing that an individual perspective could significantly improve our understanding of how commons work. Moreover, we highlight the implications of the current review for future field research in commons.